The influence of muslim organizations on the life of muslims and islam in Nigeria (2006)
The paper examines the impact of Muslim Organizations on the life of Muslims and Islam in Nigeria. It opens its discussion on early Muslim scholars reformers, Organizations and the stability of Islamic Teachings. Pre and Pro European colonization. Factors that led to the founding of contemporary. Alasalatu Groups with aims and objectives of these Muslim Organizations in Nigeria opens the main discussion of the paper. Impact of the groups on Muslims life and Islam attracts another main focus while recommendations on the areas that need to he improved spiritually and socially ends the discussion of the paper with a brief conclusion.